$$a^4 + b^4 + c^4 +l^4 = a^2b^2+a^2c^2+a^2l^2+b^2c^2+b^2l^2+c^2l^2$$ I've tried to solve this equations, have read about elliptic curves but don't know how to use it in solution. I don't know other ways to solve it.

closed as off-topic by Carl Mummert, amWhy, Taroccoesbrocco, max_zorn, Isaac Browne Jul 27 at 3:56

This question appears to be off-topic. The users who voted to close gave this specific reason:

  • "This question is missing context or other details: Please improve the question by providing additional context, which ideally includes your thoughts on the problem and any attempts you have made to solve it. This information helps others identify where you have difficulties and helps them write answers appropriate to your experience level." – Carl Mummert, amWhy, Taroccoesbrocco, max_zorn, Isaac Browne
If this question can be reworded to fit the rules in the help center, please edit the question.

  • You can write a custom solution. Only do I need it? – individ Jul 24 at 8:11

Geometrical solutions

Considering a point $A$ inside an equilateral $\Delta BCD$, denote $a=BC=CD=DB$, $b=AB$, $c=AC$ and $d=AD$. Applying cosine rule to those triangles, we may verify the following identity:

$$\fbox{$a^4+b^4+c^4+d^4=a^2 b^2+a^2 c^2+a^2 d^2+b^2 c^2+b^2 d^2+c^2 d^2$}$$

enter image description here

In particular when $b$, $c$ and $d$ are in AP, we have the following integral solutions:

$$ \begin{pmatrix} a \\ b \\ c \\ d \end{pmatrix}= \begin{pmatrix} \dfrac{(2+\sqrt{3})^{2n+2}-(2-\sqrt{3})^{2n+2}}{\sqrt{3}} \\ \dfrac{(2+\sqrt{3})^{2n+2}+(2-\sqrt{3})^{2n+2}+1}{3}- \dfrac{(2+\sqrt{3})^{n+1}-(2-\sqrt{3})^{n+1}}{\sqrt{3}} \\ \dfrac{(2+\sqrt{3})^{2n+2}+(2-\sqrt{3})^{2n+2}+1}{3} \\ \dfrac{(2+\sqrt{3})^{2n+2}+(2-\sqrt{3})^{2n+2}+1}{3}+ \dfrac{(2+\sqrt{3})^{n+1}-(2-\sqrt{3})^{n+1}}{\sqrt{3}} \end{pmatrix}$$

First of all, lose the squares: $a^2=x, b^2=y, c^2=z, l^2=t$. Then the conditions are that $x,y,z,t\geq 0$ and $x^2+x^2+z^2+t^2-xy-xz-xt-yz-yt-zt=0$.

Now I am not sure what kind of solution you expect exactly, but this equations has continuum of them. Namely, if you solve for $t$, you obtain:

$$t= \frac{(x+y+z)\pm \sqrt{3}\cdot \sqrt{2xy+2yz+2zx-x^2-y^2-z^2}}{2}$$

So if the expression $2xy+2yz+2zx-x^2-y^2-z^2$ is non-negative, which again, happens in a continuum of cases, then typically there are two solutions (at least one, since choosing the plus sign always yields a solution).

So the set of points in $\mathbb{R}^4$ is the union of two 3-dimensional manifolds.

  • This is not an approach to solving the equation. Because there's still a condition. $a=\sqrt{x}$ ; $b=\sqrt{y}$ ; $c=\sqrt{z}$ – individ Jul 24 at 9:52
  • I can see now that you meant INTEGER solutions, but this can only be implied from the tags "number theory" and "integers". Please include the condition in the post! – A. Pongrácz Jul 24 at 11:37

$$a^4+b^4+c^4+q^4=a^2b^2+a^2c^2+a^2q^2+b^2c^2+b^2q^2+c^2q^2$$

You can record such a parameterization of solutions.

$$a=p^8-16p^7s+104p^6s^2-356p^5s^3+709p^4s^4-864p^3s^5+666p^2s^6-324ps^7+81s^8$$

$$b=p^8-12p^7s+74p^6s^2-288p^5s^3+709p^4s^4-1068p^3s^5+936p^2s^6-432ps^7+81s^8$$

$$c=p^8-8p^7s+20p^6s^2-4p^5s^3-41p^4s^4-12p^3s^5+180p^2s^6-216ps^7+81s^8$$

$$q=4ps(p^2-4ps+3s^2)(3s-2p)(p-2s)(p^2-3ps+3s^2)$$

Not the answer you're looking for? Browse other questions tagged or ask your own question.